Optimasi Produksi Hydroxy Octadecadienoic Acid (HODE) dari Kapang Endofit Culvularia lunata BioMCC FE-00283 dengan Metode Respon Permukaan - ERWAHYUNI ENDANG PRABANDARI; TUN TEDJA IRAWADI; WAHONO SUMARYONO; KHASWAR SYAMSU (Fakultas Farmasi Universitas Pancasila, 2011)
Hydroxyl octadecadienoic acid (HODE) is an oxidized aliphatic fatty acid from the oxylipins group, which shows bioactivity and can be produced by Curvularia lunata BioMCC FE-00283 by submerged fermentation. Glucose, monosodium glutamate, and corn oil were media components that showed significant effect toward HODE production by C. lunata BioMCC FE-00283. Composition optimization of these three medium components was carried out by Response surface methodology (RSM). A full factorial central composite design (CCD) was used to explain the interaction effect between media components. Maximum HODE production as predicted by the quadratic model have chromatogram area of 4540000, which was verified experimentally to be 1091338 ± 152489. Eventhough experimental veriiication showed lower result compared to the model prediction, however it was higher compared to the HODE production using basal media with unoptimized composition of carbon, nitrogen, and inducer which only have chromatogram area of 295045 ± 71200. The verification also showed that optimization increased HODE production by 3.7 fold compared to that produced by the unoptimized media.